The crystal structure of 4-chloro-1H-pyrazole-3-carboxylic acid, C4H3ClN2O2 - Du DaoHang; Zhu ShiHong; Feng Chao; Jiang YunHua; Yang Jia; Tao Ting; Yu ShuLi; Zhao Hong (Zeitschrift für Kristallographie - New Crystal Structures, 2025)
C4H3ClN2O2, monoclinic, C2/c (no. 15), a = 25.4370(17) Å, b = 6.9155(5) Å, c = 13.0629(7) Å, β = 110.558 (6)°, V = 2151.6 (3) Å3, Z = 16, R gt(F) = 0.0552, wR ref(F 2) = 0.2177, T = 293 K.